The Application of a Selected Flexible Currency Risk Hedging Strategy in the Otc Market - Wybieralski, Piotr (Studia Oeconomica Posnaniensia, 2015)
The article covers the issues related to the currency risk management process within non-financial companies in the OTC market. The analysis of selected flexible hedging strategy is presented, taking into account the participation degree in positive market developments, the effective exchange rates, risk profiles and treasury limit utilization, as well as the amount of currency exposure hedged and margin call scenarios in which additional collateral is required. It is shown that especially in the highly volatile markets flexible products may become an interesting solution compared to fixed ones.